Endoscopic treatment of malignant gastric and duodenal strictures: a prospective, multicenter study - Tringali, Andrea; Didden, Paul; Repici, Alessandro; Spaander, Manon; Bourke, Michael J.; Williams, Stephen J.; Spicak, Julius; Drastich, Pavel; Mutignani, Massimiliano; Perri, Vincenzo; Roy, André; Johnston, Krystal; et al. (Gastrointestinal endoscopy, 2014)
Malignant gastric outlet obstruction is often treated by stent placement. To investigate the outcomes of stent placement in the palliative treatment of malignant neoplasms. Prospective, observational, multicenter registry. Six tertiary care centers in 5 countries. A total of 108 adult patients with malignant gastric outlet obstruction. Placement of an uncovered, self-expandable, metal duodenal stent. The primary endpoint was stent patency at 14 days after stent implantation. Secondary endpoints included stent patency at 1, 2, 3, and 6 months, gastric outlet obstruction scoring system (GOOSS) scores at 14 days and 1, 2, 3, and 6 months after stent deployment, technical success, adverse events, and patient survival (ie, confirmed duration of the implant). Technical success was achieved in 99.1% of stent placements. Stent patency at 14 days was 94.6%. Kaplan-Meier estimates of stent patency were 92.9% at 1 month, 86.2% at 2 months, 81.9% at 3 months, and 63.4% at 6 months. At 14 days, GOOSS scores increased by a median of 1 point. The overall GI adverse event rate was 32.4%; however, the stent-related adverse event rate was 19.4%. The median implant duration was 47 days (range 0-195 days). Observational study, no control group. Duodenal stent placement resulted in prompt relief of malignant gastric outlet obstruction and improved GOOSS scores. (Clinical trial registration number: NCT00991614.)